Systemic decision making : fundamentals for addressing problems and messes - Hester, Patrick T.; Adams, Kevin MacG (Springer, 2017)
This expanded second edition of the 2014 textbook features dedicated sections on action and observation, so that the reader can combine the use of the developed theoretical basis with practical guidelines for deployment. It also includes a focus on selection and use of a dedicated modeling paradigm -- fuzzy cognitive mapping -- to facilitate use of the proposed multi-methodology. The end goal of the text is a holistic, interdisciplinary approach to structuring and assessing complex problems, including a dedicated discussion of thinking, acting, and observing complex problems. The multi-methodology developed is scientifically grounded in systems theory and its accompanying principles, while the process emphasizes the nonlinear nature of all complex problem-solving endeavors. The authors' clear and consistent chapter structure facilitates the book's use in the classroom.
Keywords: System theory.; Decision making.; elektronické knihy; electronic books